2023
DOI: 10.1001/jamanetworkopen.2023.41928
|View full text |Cite
|
Sign up to set email alerts
|

Early Integrated Palliative Care Within a Surgical Oncology Clinic

Varun V. Bansal,
Daniel Kim,
Biren Reddy
et al.

Abstract: ImportanceAdvance directive (AD) designation is an important component of advance care planning (ACP) that helps align care with patient goals. However, it is underutilized in high-risk surgical patients with cancer, and multiple barriers contribute to the low AD designation rates in this population.ObjectiveTo assess the association of early palliative care integration with changes in AD designation among patients with cancer who underwent surgery.Design, Setting, and ParticipantsThis cohort study was a retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…While prior literature has described preoperative advance directive designation, this initiative was the first to our knowledge to implement a more comprehensive goals of care conversation, including PV questions, in the preoperative ambulatory setting. 34 Second, we demonstrated that clinicians and patients perceived these goals of care conversations positively, which can promote further work to integrate these discussions into standard of care for surgical patients, especially those undergoing cancer surgery.…”
Section: Discussionmentioning
confidence: 74%
“…While prior literature has described preoperative advance directive designation, this initiative was the first to our knowledge to implement a more comprehensive goals of care conversation, including PV questions, in the preoperative ambulatory setting. 34 Second, we demonstrated that clinicians and patients perceived these goals of care conversations positively, which can promote further work to integrate these discussions into standard of care for surgical patients, especially those undergoing cancer surgery.…”
Section: Discussionmentioning
confidence: 74%
“…Colonoscopy should also be performed in all patients. Patients should be referred to patient support groups, financial support, fertility counseling, psychosocial support, and social work as indicated [29] [30].…”
Section: Block 1: Initial Management and Preoperative Considerationsmentioning
confidence: 99%
“…8,55 Early specialist palliative care consultation is encouraged to facilitate multidisciplinary management of symptoms and supportive care needs across the patient's disease course. [56][57][58] For patients with subacute presentations such as chronic or recurrent bowel obstruction, consideration of discussion at a multidisciplinary tumor board is proposed when possible.…”
Section: Block 1 (Agreement: Round I -97% Round Ii -98%)mentioning
confidence: 99%